Determinants of Exclusive Breastfeeding to 0-6 Month Babies in Stunting Handling in The District of Kupang - Ina Debora Ratu Ludji (Eduvest - Journal of Universal Studies, 2024)
Stunting is a form of failure to thrive at high altitude (stunting) due to accumulation of malnutrition that persists from conception to 24 months of age (Bloem et al, 2013). This situation is exacerbated by insufficient catch-up growth (Kusharispeni, 2002). The index for identifying stunted young children is based on the age index (TB/U) according to the WHO criteria (2015). -2 standard deviations (SD). The aim of this study was to analyze the determinants of exclusive breastfeeding at 0-6 months of age to prevent stunting in NTT's Kupang County. This type of study is quantitative with a cross-sectional design. The study population consisted of breastfeeding mothers and infants aged 0-6 months from Kupang District, East Nusa Tenggara. The sample was a breastfeeding mother aged 0–6 months who met the inclusion criteria, i.e., live birth willing to be a respondent, single birth, nondisabled, free of comorbidities mothers and infants. was an infant. The number of samples is 75. The sampling technique is cluster random sampling. Results showed that there was no significant association between respondents' workplace characteristics and incidence of stunting, p=0.21 >α=0.05. There are important relationships. Age p=0.0001 <; = 0.05; Education 0.028 <; α = 0.05 Knowledge p = 0.003 <; = 0.05; Role p = 0.0001 <; = 0.05. It was concluded that age, education, knowledge, family support, officer role, and family role were determinants of exclusive breastfeeding to prevent stunting. We recommend using this model to prevent growth retardation.